156 A prospective audit of symptom burden and palliative care referral amongst in-patients with decompensated liver disease. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Brown-Kerr, A; Trolland, D; Hay, I; Barclay, S; Finlay, F
Abstract : Aim: Previous studies have suggested an unmet symptom burden in patients with decompensated chronic liver disease (DCLD). The Bristol Prognosis Score (BPS) has been designed to identify patients with DCLD likely to be in the last year of their life, who may benefit from Specialist Palliative Care team input. We aimed to audit the prevalence of symptoms appropriate to trigger referal to the Hospital Specialist Palliative Care Team (HSPCT), (using the Integrated Palliative care Outcome Score (IPOS)), rates of recognition of these by physicians, and rates of referral to HPSCT according to BPS status. Methods: A prospective audit of all inpatients with DCLD admitted over 3 months was conducted. Patients completed IPOS questionnaires. Demographic data were collated in order to calculate BPS. Case notes were reviewed following discharge to assess if significant symptoms (regarded as scoring ‰¥ 2 on IPOS) were identified by the medical team. Referral rates to HSPCT were also recorded. Results: 40 patients with DCLD were included. 36 (90%) scored ‰¥2 in at least one IPOS category. Most patients (20(55.6%)) had only some of their significant symptoms recognised by medical staff. 27/40 (67.5%) patients were BPS positive. Of these only 1 (3.7%) was referred to HSPCT. Conclusions: This work demonstrates a significant symptom burden in patients with DCLD. This does not appear to be recognised by the medial team, meaning referral rates to HSPCT are low. Routine use of the IPOS in conjunction with BPS may aid identification and referral of patients to HSPCT, and help address this.